Penerapan konseling behavioristik dengan teknik self management untuk mengatasi perilaku membolos pada siswa kelas XI - Wijayanti, Nurhasanah Laras Putri; Ratnasari, Devi (Universitas Indraprasta PGRI, 2024)
this study aims to find out about the application of behavioristic counseling with self management techniques to overcome truancy behavior in grade XI students. The research method used in this study is quantitative research with an experimental research method using pre-experiment, one group pre-test and post-test design. The data and data sources in this study are students of class XI SMK Panca Karya Sentul, the total population is 55 students using purposive sampling techniques. The instrument used is a questionnaire adapted from a thesis that is relevant to the research. The data analysis technique was carried out by using the paired sample t test. The results of the study concluded in general that group counseling services with self-management techniques were effective in reducing truancy behavior in students. The results of this study are useful for schools in designing group counseling service programs to effectively help reduce truancy behavior in students.